Enzymatic recovery of rhodium(III) from aqueous solution and industrial effluent using sulphate reducing bacteria: role of a hydrogenase enzyme - Ngwenya, Nonhlanhla (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2005)
In an attempt to overcome the high maintenance and costs associated with traditional physico-chemical methods, much work is being done on the application of enzymes for the recovery of valuable metals from solutions and industrial effluents. One of the most widely studied enzymatic metal recovery systems uses hydrogenase enzymes, particularly from sulphate reducing bacteria (SRB). While it is known that hydrogenases from SRB mediate the reductive precipitation of metals, the mechanism of enzymatic reduction, however, is not yet fully understood. The main aim of the present study was to investigate the role of a hydrogenase enzyme in the removal of rhodium from both aqueous solution and industrial effluent. A quantitative analysis of the rate of removal of rhodium(III) by a resting SRB consortium under different initial rhodium and biomass concentrations, pH, temperature, presence and absence of SRB cells and electron donor, was studied. Rhodium speciation was found to be the main factor controlling the rate of removal of rhodium from solution. SRB cells were found to have a higher affinity for anionic rhodium species, as compared to both cationic and neutral species, which become abundant when speciation equilibrium was reached. Consequently, a pH-dependant rate of rhodium removal from solution was observed. The maximum SRB uptake capacity for rhodium was found to be 66 mg rhodium per g of resting SRB biomass. Electron microscopy studies revealed a time-dependant localization and distribution of rhodium precipitates, initially intracellularly and then extracellularly, suggesting the involvement of an enzymatic reductive precipitation process. A hydrogenase enzyme capable of reducing rhodium(III) from solution was isolated and purified by PEG, DEAE-Sephacel anion exchanger and Sephadex G200 gel exclusion. A distinct protein band with a molecular weight of 62kDa was obtained when the hydrogenase containing fractions were subjected to a 10% SDS-PAGE. Characterization studies indicated that the purified hydrogenase had an optimum pH and temperature of 8 and 40Â°C, respectively. A maximum of 88% of the initial rhodium in solution was removed when the purified hydrogenase was incubated under hydrogen. Due to the low pH of the industrial effluent (1.31), the enzymatic reduction of rhodium by the purified hydrogenase was greatly retarded. It was apparent that industrial effluent pretreatment was necessary before the application an enzymatic treatment method. In the present study, however, it has been established that SRB are good candidates for the enzymatic recovery of rhodium from both solution and effluent.
Keywords: Enzymes; Rhodium; Enzymes -- Industrial applications; Sulfur bacteria; Hydrogenation; Hydragenase; Factory and trade waste -- Purification